The mechanosensitive TRPV2 calcium channel promotes human melanoma invasiveness and metastatic potential. (6th February 2023) - Shoji, Kenji F; Bayet, Elsa; Leverrier‐Penna, Sabrina; Le Devedec, Dahiana; Mallavialle, Aude; Marionneau‐Lambot, Séverine; Rambow, Florian; Perret, Raul; Joussaume, Aurélie; Viel, Roselyne; Fautrel, Alain; Khammari, Amir; et al.
Abstract: Melanoma is a highly aggressive cancer endowed with a unique capacity of rapidly metastasizing, which is fundamentally driven by aberrant cell motility behaviors. Discovering "migrastatics" targets, specifically controlling invasion and dissemination of melanoma cells during metastasis, is therefore of primary importance. Here, we uncover the prominent expression of the plasma membrane TRPV2 calcium channel as a distinctive feature of melanoma tumors, directly related to melanoma metastatic dissemination. In vitro as well as in vivo, TRPV2 activity is sufficient to confer both migratory and invasive potentials, while conversely TRPV2 silencing in highly metastatic melanoma cells prevents aggressive behavior. In invasive melanoma cells, TRPV2 channel localizes at the leading edge, in dynamic nascent adhesions, and regulates calcium‐mediated activation of calpain and the ensuing cleavage of the adhesive protein talin, along with F‐actin organization. In human melanoma tissues, TRPV2 overexpression correlates with advanced malignancy and poor prognosis, evoking a biomarker potential. Hence, by regulating adhesion and motility, the mechanosensitive TRPV2 channel controls melanoma cell invasiveness, highlighting a new therapeutic option for migrastatics in the treatment of metastatic melanoma. Synopsis: The mechanosensitive TRPV2 channel positively regulates the invasive potential and metastatic dissemination of melanoma cells, providing a new biomarker and potential migrastatic target for cutaneous metastatic melanoma. TRPV2 is predominantly expressed in metastatic melanoma cells and tissues where it stands out as the most expressed calcium channel. Malignant melanoma tumor cells harbor active TRPV2 channels at their surface that drive their invasive behavior and metastatic potential. Mechanistically, TRPV2 controls melanoma cell dissemination by activating the Ca 2+ ‐sensitive protease calpain and acting on nascent adhesion structures dynamics. In human melanoma, TRPV2 expression is exacerbated compared to benign nevi and associated with poor survival. Abstract : The mechanosensitive TRPV2 channel positively regulates the invasive potential and metastatic dissemination of melanoma cells, providing a new biomarker and potential migrastatic target for cutaneous metastatic melanoma.